TATA LETAK DAN KOMUNIKASI RUANG OUTLET VNC, SENAYAN CITY - Liza Dwi Ratna Dewi; Hendari Oktaviani (Communication, 2012)
This research aims to find out how the layout and space communications providing in VNC outlet  Senayan City, And what message is being delivered to customers via VNC layout and space communications in the customer service outlets providing VNC, Senayan City.Theories used in research is the theory of Edward Hall, about the existence of intimate, personal, social distance is the distance, the distance of the public. According to Astrid Kusumowidagdo in his book the design of Retail (57: 2011) on the layout, i.e. Selling Space Space, Personnel, Merchandising Space, Customer Space. Because according to Shannon and Weaver (1949) that the communication is a form of interaction that interplay with each other, deliberate or accidental. Not tebatas in the form of communication using verbal language, but also in terms of expression, painting, art, and technology (nonverbal).The method  of research is case studies with one case and multi unit of analysis. The collection of data obtained by the author with conducting research through participant observation in the natural situation of the research object of VNC, Senayan City outlets. Analysis of case studies on non-verbal communication when it is associated with this research is to describe How the layout and Space Communications Officer in the customer service Outlets Providing VNC, Senayan CityThe results showed a space communications outlets used VNC, Senayan City in providing services at the customer's personal distance communication, social distance, the distance of the public. With the consumer is not a mutual tangent with the officer and fellow visitors when dealing in the Outlet. The layout and space communication in the service of customers to note. The layout of individual items and accessories of other supporters have long distance interaction, where the customer can turned his attention to the products and services by making your employees satisfaction through comfort level optimal space. Harmony in structuring the space created when there is balance and alignment of the materials described above. The room must always provide a safe, healthy and peaceful, memorable.A summary of the results of this research is a communications space are good or comfortable reflected from the good and the room comfortable. Theoretical advice on non-verbal communication through layout and communications space spatial expressed very ease understanding of Edward Hall's condition through the distance and cue-cue. Practical advice so that the public understand the layout and space in daily communication in interacting with behaves the opposite communication. The layout of individual items and accessories of other supporters have long distance interaction, where the customer can turned his attention to the products and service by the employee so as to make optimal satisfaction through comfort level that was formed through the layout and communications space.